The associations between physical activity, microbiome and metabolic adaptation in sedentary overweight adults - Av, Eylam Ziv; Greenberg, Alisa; Knaan, Tzachi; Melanson, Edward L.; Youngster, Ilan; Dubnov-Raz, Gal; Borenstein, Elhanan; Gepner, Yftach (Frontiers in Nutrition, 2026)
Despite well-established benefits of exercise on metabolic regulation and the gut microbiome (GM), its impact on body composition is inconsistent and often attenuated by metabolic adaptation. This compensation mechanism adjusts energy expenditure including total daily energy expenditure (TDEE) and resting metabolic rate (RMR). Intra-individual variation in exercise response remains unclear, but might be explained by the GM. In this well-controlled study, we investigated the relationship between aerobic exercise, GM composition, and metabolic adaptation in a cohort of 16 sedentary overweight adults (ages 21–45, 50% female) over a 12-week moderate-intensity intervention (65–75% HRmax; 20 kcal/kg/week). Pre- and post-intervention RMR was measured via whole-room calorimetry, TDEE by doubly labeled water, and GM composition via shotgun metagenomics. While body composition did not change at the group-level, a subset of participants (“responders”) showed improved body composition and aerobic capacity. Using machine learning, we identified bacterial species, including Faecalibacterium prausnitzii species, whose abundance pre-training is predictive of response. Additionally, we found that responder GM communities are more compositionally cohesive and post-training increases in GM diversity are associated with higher TDEE and RMR. These findings highlight the complex interaction between exercise, metabolism and the GM, and suggest that baseline GM characteristics may contribute to individual variability in metabolic adaptation. This insight may help guide microbiome-informed strategies to enhance exercise efficacy.Clinical trial registration: ClinicalTrials.gov, identifier NCT04460040.